Deer antler velvet (Cervus elaphus sibiricus) promotes fracture healing via partial BMP2-Smad mediated osteoblast differentiation - Ji Hyang Gu; Min-Young Chae; Jeong June Choi; Thanh Chu Duc; Chang Gue Son; Eun-Jung Lee (Journal of Orthopaedic Surgery and Research)
Abstract Background Cervus elaphus Sibiricus (CES) has been traditionally used in Korean clinics to promote fracture healing based on its function of tonifying the kidneys and strengthening bones. However, experimental data supporting its efficacy are still insufficient. The aim of this study investigated the bone-union properties of CES in a femoral fracture animal model and its corresponding molecular mechanisms. Methods Fifty-four C57BL/6 male mice underwent femoral shaft fracture by Bonnarens and Einhorn’s method, subsequently receiving a water extract of CES (200 mg/kg/day, daily) for 7 and 14 days. Safranin O staining and immunohistochemistry of the fracture region were conducted against transforming growth factor-β (TGF-β), bone morphogenetic protein 2 (BMP2), and osterix. MG63 cells used to examine the underlying mechanisms of CES focused on BMP2-Smad pathway-related osteogenesis. Results CES administration led to earlier union of the fractured bones, supported by Safranin O staining of the fracture region, demonstrating significantly increased cartilage formation day on 7 and a rapidly decreased cartilage area due to callus formation day on 14. CES administration also significantly upregulated the expression of TGF-β1 day 7, BMP 2, and osterix day 14 at the fracture site and also up-regulated alkaline phosphatase (ALP) activity, calcium deposition, and the phosphorylation of Smad in MG63 cells. Conclusions CES promotes fracture healing by promoting osteoblastogenesis via a partial BMP2-Smad pathway.